Wyzwania stojące przed ubezpieczycielami w kontekście programu Solvency II - Gątkowski, Mateusz (The Challenges the Insurance Companies Have to Face in the Context of "The Solvency II Program", 2006)
The Solvency II is aimed to change present solvency regime in the European Union and create a solvency system adjusted to the range of risks that insurance undertakings are facing. Changes are necessary in order to tailor legislation to quickly changing insurance market, to the developments in risk and finance management techniques, to changes in financial reporting standards. The program will influence activities of insurers. Simulation methods will evolve, the demand on well-structurised, good quality data will increase, role of actuaries in companies will be broadened. It is expected that new directives of European Commission will be implemented by the end of the present decade. Compliance effort and costs will be significant for insurers, it is expected that investments in IT systems and data management procedures, preparatory work on simulation models, accumulating appropriate skills in the company, providing employees with trainings on regulatory changes, will be required. Polish insurance market due to short modem history will be even more exposed to the Solvency II challenges.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1108, s. 130-142